According, against, and above dietary norms: a key to understanding the relationship between personality style and taste preferences - Ligiana Mihaela Petre; Bianca Nicoleta Vatasescu (PeerJ, 2019)
Background Understanding individual food preferences is critical for creating tailored strategies that promote healthy individual eating behaviors. Individual sensory liking appears to be an essential determinant of dietary intake. Taste preferences influence satisfaction and satiety, and may consequently influence weight status and psychological adjustment. The purpose of this study was to identify the association between taste preferences (sweet, salty, sweet & fatty, salty & fatty) and personality features. Methods The Millon Clinical Multiaxial Inventory-III (MCMI-III) was used for the assessment of personality traits and PrefQuest (PQ) was used for measuring recalled food preferences. A total of 137 participants were included in the study. The relationship between compulsive and antisocial features and taste preferences was assessed by hierarchical multiple linear regression, while controlling for age, gender, BMI, marital status, and educational level. Results The antisocial personality traits were a negative explanatory variable for sweet & fatty taste preference, R2 = .15, t(132) =  − 2.40, p = .018, 95% [−.57, −.06] and salty & fatty taste preference, R2 = .16, t(133) =  − 2.38, p = .019, 95% [−.07, −.01], while controlling for anthropological factors. In addition, men showed a higher preference than women for sweet & fatty food, such as chocolate or desserts, rsp = .19, p = .021, and for the salty & fatty food, rsp = .30, p < .001. BMI was not found to moderate the relationship between personality and taste preference. No significant association was found between compulsive personality traits and food preference, as assessed by sensory liking. Conclusions The findings can bring a much better understanding of the relationship between the compulsive or antisocial personality and taste preferences. In addition, it may help build psychotherapeutic and nutritional strategies that promote healthy eating behaviors, tailored to a particular personality style.